Characterization of Chelation and Absorption of Calcium by a Mytilus edulis Derived Osteogenic Peptide - Xu, Zhe; Han, Shiying; Chen, Hui; Zhu, Zhixuan; Han, Lingyu; Dong, Xiufang; Du, Ming; Li, Tingting (Frontiers in Nutrition, 2022)
In a previous study, the peptide LGKDQVRT, which was identified by enzymatic hydrolysis, released during the proteolysis of Mytilus edulis, had potential osteogenic activity. In this study, the octapeptide LGKDQVRT was able to spontaneously bind calcium in a 1:1 stoichiometric ratio, and the calcium-binding site likely involves calcium and amino acid VAL6 in the LGKDQVRT peptide to form a metal-donor to metal acceptor complex. The peptide LGKDQVRT has the activity of promoting the proliferation and differentiation of osteoblasts. The results of this study suggest that hydrolyzed peptides from Mytilus edulis protein can be used as a dietary supplement to improve calcium absorption and prevent osteoporosis.